Future energy challenge, opportunity, and, sustainability - Wang, Xiaolin (Springer, 2023)
Future Energy: Challenge, Opportunity, and Sustainability presents new advances and research results in the fields of theoretical, experimental, and practical sustainable energy engineering. The book’s chapters are based on selected research papers presented at the 2023 7th International Conference on Sustainable Energy Engineering (ICSEE 2023). Contributions cover case studies to explore and analyze technological advancements alongside practical applications to help readers better understand the relevant concepts and solutions necessary to achieve clean energy and sustainable development. The book brings together the latest developments in the emerging areas of intelligent power systems, green energy, and technology. It offers approaches to help engineers and researchers working in sustainable energy engineering technologies solve practical problems affecting their daily work
Keywords: bicssc; bisacsh; Electric power distribution; Electric power-plants; Sustainability; Energy policy; Energy and state; Renewable energy sources; Hardcover, Softcover / Technik/Wärmetechnik, Energietechnik, Kraftwerktechnik